(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, in preparation for equipment failure of emergency broadcasting equipment, we intend to propose a method to respond in advance to situations where abnormalities are visible.In the case of a short circuit in the speaker line in the emergency broadcasting system, high current from the power amplifier enters the line again and damages the power amplifier, making audio output impossible. As a method to prevent this, a method of separating the speaker line from other lines is mainly used in order not to affect other speaker lines when a short circuit occurs.In this study, a method for establishing a safety system with a higher level than the standard recommended by the government in emergency broadcasting system was studied and suggested. The method is to respond in advance by monitoring and analyzing the prognostic symptoms that appear before the actual failure occurs.For example, if a problem occurs in the system, the problem is solved by replacing the part or removing the time factor of the problem. However, before a failure occurs, there are cases in which the occurrence and cancellation of failure symptoms for a short period of time occur periodically or aperiodically. In this case, the possibility of actual failure is determined in advance by analyzing it as a precursor to the actual failure.In the event of a situation that appears to be a pre-specified potential failure, we propose techniques to diagnose it early and tell the manager how to take action.